Smart Curriculum Mapping: A Blockchain Approach to Transparent and Customizable Educational Pathways - Chen Mei; Sofia Lim; Ananya Rao (Journal of Paddisengeng Technology, 2025)
Background. Traditional curriculum mapping often faces challenges of transparency, flexibility, and personalization. Existing digital systems tend to be centralized, limiting stakeholder trust and adaptability in designing individualized learning trajectories. Blockchain technology offers an innovative solution to ensure transparency, immutability, and decentralized control over educational data, enabling both institutions and learners to co-create customizable educational pathways. Purpose. This study aimed to investigate the potential of blockchain-based smart curriculum mapping in fostering transparent governance of curricula and supporting adaptive learning designs. Specifically, it examined how blockchain can integrate institutional requirements with learner-driven customization while ensuring accountability and security. Method. Using a mixed-method design, the research engaged 210 university students and 45 lecturers across three higher education institutions. Data were collected through surveys, interviews, and prototype testing of a blockchain-enabled curriculum mapping platform. The findings were analyzed using statistical methods and thematic coding to evaluate user perceptions, system usability, and pedagogical impact. Results. The findings indicate that blockchain-based curriculum mapping enhances trust among stakeholders by ensuring transparent records of course progress and requirements. Students reported increased autonomy in designing personalized pathways, while lecturers emphasized the benefits of immutable documentation for accreditation and evaluation. However, challenges such as technical literacy and system scalability were also identified. Conclusion. This study highlights the transformative role of blockchain in curriculum management. By integrating transparency, security, and learner-centered customization, smart curriculum mapping offers a scalable model for future educational governance. The findings contribute to both educational technology innovation and institutional policy-making, offering pathways toward more accountable and personalized higher education systems.